Sonochemical synthesis, crystal structure, and DFT calculation of an innovative nanosized Pb(II)-azido metal–organic coordination polymer as a precursor for preparation of PbO nanorod - Hanifehpour, Younes; Mirtamizdoust, Babak; Ahmadi, Hossein; Wang, Ruiyao; Joo, Sang Woo (Chemical papers, 2020)
A sonochemical synthesis was performed to synthesize nanosheets of an innovative lead (II) metal–organic coordination polymer (CP) [(PbN 3 Q) 2 ] n ( 1 ) (Q – = 8-hydroxyquinolinate). For precise characterization, scanning electron microscopy, elemental analysis, IR spectroscopy, X-ray powder diffraction, and single-crystal X-ray diffraction scrutiny were conducted. The X-ray structural examination indicated that 1 was a 1D chain with the two neighboring Pb(II) centers bridged together by two O atoms from two Q − ligands and two N 3 − using their two terminal N atoms. Pb(II) had a coordination number of 7 with an asymmetrical coordination geometry. The contiguous chains were linked by the π – π interactions with the aromatic circles of Q − from the chains adjacent to each other. Therefore, these weak interactions facilitated the construction of a 3D metal–organic CP using the basic 1D building block. Density functional theory was used to optimize the title complex structure. The computed natural bond orbital burdens suggested that its ascription to the Pb…Pb contacts in the chains may have been attributed to the scant positive burden in the lead (II) ions. In summary, PbO nonorods were simply synthesized by thermolysis of 1 at 180 °C using oleic acid as the surfactant.